2010
DOI: 10.1021/es9034123
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 4-Nitrophenol, 2-Chloro-4-nitrophenol, and 2,4-Dinitrophenol by Rhodococcus imtechensis Strain RKJ300

Abstract: A bacterial strain Rhodococcus imtechensis RKJ300 (= MTCC 7085(T) = JCM 13270(T)) was isolated from pesticide-contaminated soil of Punjab by the enrichment technique on minimal medium containing 4-nitrophenol. Strain RKJ300 is capable of utilizing 4-nitrophenol, 2-chloro-4-nitrophenol, and 2,4-dinitrophenol as sole sources of carbon and energy. The strain involved both oxidative and reductive catabolic mechanisms for initial transformation of these compounds. In the case of 2-chloro-4-nitrophenol, colorimetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
87
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 42 publications
2
87
0
Order By: Relevance
“…To our surprise, BT was identified as the ring cleavage substrate during 2C4NP degradation in this strain, rather than HQ as previously proposed (4). On the other hand, the two-component (TC) para-nitrophenol (PNP) monooxygenase PnpA1A2 in this strain was found to be able to catalyze the sequential denitration and dechlorination of 2C4NP to BT, and pnpA1 is essential for strain RKJ300 to utilize 2C4NP and PNP.…”
mentioning
confidence: 44%
See 2 more Smart Citations
“…To our surprise, BT was identified as the ring cleavage substrate during 2C4NP degradation in this strain, rather than HQ as previously proposed (4). On the other hand, the two-component (TC) para-nitrophenol (PNP) monooxygenase PnpA1A2 in this strain was found to be able to catalyze the sequential denitration and dechlorination of 2C4NP to BT, and pnpA1 is essential for strain RKJ300 to utilize 2C4NP and PNP.…”
mentioning
confidence: 44%
“…strain SJ98 (14). However, no such information has been reported in Gram-positive bacteria, although two Gram-positive 2C4NP utilizers (4,5) were isolated. In this study, the high transcription of the pnp cluster in 2C4NP-and PNP-induced cells indicated that the enzymes encoded by the pnp genes were likely involved in both 2C4NP catabolism and PNP catabolism in strain RKJ300.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of comparative genomics suggest that homologs of these proteins are exclusively encoded by the genera Nocardioides, Rhodococcus, and Nocardia among presently sequenced organisms. Empirical studies consistently indicate that equivalent enzymatic pathways can degrade nitroaromatic compounds in five additional Rhodococcus species (398,(436)(437)(438) and three Nocardioides species (54,396,397,432,439). Beyond picrate and 2,4-dinitrophenol, LLHTs are involved in the biodegradation of other nitroaromatic compounds.…”
Section: Fdors: Flavin/deazaflavin Oxidoreductase Superfamilymentioning
confidence: 96%
“…The microbial degradation of NACs has been extensively investigated (15,32,40,41). Although structurally related to the NACs, the CNACs are extremely resistant (12,31,49,50,51) to microbial degradation due to the simultaneous existence of two strong electron-withdrawing chlorine and nitro groups; thus, the knowledge of its microbial degradation is very limited. Most investigations of the degradation of CNACs have revealed cometabolic transformations.…”
mentioning
confidence: 99%